1990
DOI: 10.2136/sssaj1990.03615995005400030007x
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Conductivity of Porous Media at Low Water Content

Abstract: Matric potential ψ and hydraulic conductivity K at low water content θ often obey power laws in θ, but the exponents of these are largely empirical. Theories of fractal geometry and of thin‐film physics provide a basis for the observed power‐law behavior of ψ and K. Specifically, they lead to ψ ∝ θ−1/(3‐D) and K ∝ θ3/m(3 − D), where D is the Hausdorff dimension of the surface between the pore space and grains or matrix, and m is the exponent in the relation of disjoining pressure II and film thickness h, i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(72 citation statements)
references
References 0 publications
2
69
1
Order By: Relevance
“…In addition, adsorptive forces between water and matrix lead to the formation of a thin water film at the rock-air interface. Such water films with a thickness typically below 20 nm (e.g., Toledo et al, 1990;Tokunaga and Wan, 1997) exhibit very short NMR relaxation times. Although water films to some extent may influence transport properties and water distribution of a partially saturated porous system (Tuller and Or, 2001), the contribution of the film volume to NMR amplitudes is very small with respect to the NMR signal amplitudes arising from the water trapped in the menisci; i.e., V film V meniscus .…”
Section: Water Distribution During Drainage and Imbibition In A Partimentioning
confidence: 99%
“…In addition, adsorptive forces between water and matrix lead to the formation of a thin water film at the rock-air interface. Such water films with a thickness typically below 20 nm (e.g., Toledo et al, 1990;Tokunaga and Wan, 1997) exhibit very short NMR relaxation times. Although water films to some extent may influence transport properties and water distribution of a partially saturated porous system (Tuller and Or, 2001), the contribution of the film volume to NMR amplitudes is very small with respect to the NMR signal amplitudes arising from the water trapped in the menisci; i.e., V film V meniscus .…”
Section: Water Distribution During Drainage and Imbibition In A Partimentioning
confidence: 99%
“…This was attributed to the impact of the distribution of smaller pores, and this topic shall be recalled within the present paper, as well. It is well known that at high water contents the WRC is governed by the distribution of larger pores, while at the low water contents the WRC is determined by the thin water film on the solid particles [11] [14] [15]. This naturally calls for a two-fold fractal interpretation of the retention process.…”
Section: The Two Regimes Fractal Modelmentioning
confidence: 99%
“…In the past years, an important boost came from the fractal geometry [6]- [8] which was used to characterize the hydraulic conductivity by means of the fractal properties of pore spaces ([9] [10]). This has permitted relating the fractal dimension at low water content values to the physics of thin water films [11] either by combining Kock's curve to the flow (Poiseuille) equation [12], or by dealing with the fractal dimension of the porosity and a diffusion-type (Millington and Quirk) equation [13]. An exhaustive review of all these models can be found in ( [14] [15] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical results for the dependence of the relative permeability of the wetting phase under conditions of film flow were obtained by de Gennes, 6 Novy, 7 and Toledo. 8 In the thick-film flow regime, de Gennes' theory predicts an exponent of the form (see Toledo et al 8 ). For values of D on the order of 2.3 to 2.6 and m‫ס‬ 1 ⁄2, one obtains estimates for b in the range 8.4 to 16.8.…”
Section: Introductionmentioning
confidence: 99%